2017
DOI: 10.4253/wjge.v9.i6.273
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter randomised controlled trial comparing the high definition white light endoscopy and the bright narrow band imaging for colon polyps

Abstract: AIMTo compare high definition white light endoscopy and bright narrow band imaging for colon polyps’ detection rates.METHODSPatients were randomised to high definition white light endoscopy (HD-WLE) or the bright narrow band imaging (bNBI) during withdrawal of the colonoscope. Polyps identified in either mode were characterised using bNBI with dual focus (bNBI-DF) according to the Sano’s classification. The primary outcome was to compare adenoma detection rates (ADRs) between the two arms. The secondary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Similar results of longer withdrawal time in the NBI arm were noted in previous randomized controlled trials and meta‐analyses. 36 , 42 , 43 It is well‐established that increased withdrawal time leads to improved PDR (as in this study) and ADR. 37 Since the withdrawal time in the NBI group was longer compared to HD‐WL, one would have expected that the NBI arm should have performed better than HD‐WL in terms of ADR and PDR.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Similar results of longer withdrawal time in the NBI arm were noted in previous randomized controlled trials and meta‐analyses. 36 , 42 , 43 It is well‐established that increased withdrawal time leads to improved PDR (as in this study) and ADR. 37 Since the withdrawal time in the NBI group was longer compared to HD‐WL, one would have expected that the NBI arm should have performed better than HD‐WL in terms of ADR and PDR.…”
Section: Discussionsupporting
confidence: 59%
“…An earlier study found that one operator had a significantly enhanced ADR using NBI while two others did not. 43 Thus, operators could also have had different baseline ADRs, and adapted to using NBI differently over time. Moreover, patients were randomized to each modality in a 1:1 ratio in blocks of 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of additional detection of HP and adenomas in the WLI-LCI group were also higher than in the LCI-WLI group. Since these polyps are easily detectable due to their protruding morphology, detection by WLI may be sufficient 26 . The value of LCI for the detection of these polyps should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Disadvantages of the use 11 of exogenous markers include potentially unequal distribution, pooling which can obscure lesions, and lengthening of 12 the duration of the procedure 51 . These imaging modalities have also been integrated into CE [52][53][54][55] but studies have 13 cast doubt on their efficacy compared with standard WLI capsules [56][57][58][59] . Other alternative imaging technologies such 14 as µUS, fluorescent imaging and OCT address some of the limitations associated with WLI technology.…”
mentioning
confidence: 99%